2021
DOI: 10.1136/bmjopen-2021-053819
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and use of mHealth home telemonitoring in adults with acute COVID-19 infection: a scoping review protocol

Abstract: IntroductionmHealth refers to digital technologies that, via smartphones, mobile apps and specialised digital sensors, yield real-time assessments of patient’s health status. In the context of the COVID-19 pandemic, these technologies enable remote patient monitoring, with the benefit of timely recognition of disease progression to convalescence, deterioration or postacute sequelae. This should enable appropriate medical interventions and facilitate recovery. Various barriers, both at patient and technology le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…They found that although several wound care apps are available for nurses to use, there is a lack of rigorous and standardized evaluations of these apps, few clinical trials, and a paucity of information about which apps nurses actually use in real time [ 28 ]. A scoping review by Dauletbaev et al [ 29 ] highlighted the increased the use of mHealth telemonitoring for patient care since the COVID-19 pandemic, a trend we also saw in-home health. Although both reviews highlight the importance of technology for the health care workforce and patient care, neither review included HHAs.…”
Section: Discussionmentioning
confidence: 99%
“…They found that although several wound care apps are available for nurses to use, there is a lack of rigorous and standardized evaluations of these apps, few clinical trials, and a paucity of information about which apps nurses actually use in real time [ 28 ]. A scoping review by Dauletbaev et al [ 29 ] highlighted the increased the use of mHealth telemonitoring for patient care since the COVID-19 pandemic, a trend we also saw in-home health. Although both reviews highlight the importance of technology for the health care workforce and patient care, neither review included HHAs.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitated adaptation of a system that was in an early phase of development that used devices designed for remote monitoring of relatively healthy ambulant people in the community (Nguyen Van Vinh Chau, 2022). While systems using similar equipment have been used for collecting data from individuals suffering from COVID in community settings (Dauletbaev et al, 2021), the re-purposing of this equipment for use in wards with very sick patients is much less common. Filho et al (Filho et al, 2021) describe a proof of principle deployment of a bespoke monitoring system designed for ICU settings on an ICU ward in Brazil.…”
Section: Rapidly Adapting Technology To An Icu Settingmentioning
confidence: 99%
“…Need for digital wisdom (Kruse et al, 2020;Ruberti et al, 2021) ii. Lack of computer/digital skills (Dauletbaev et al, 2021;Middlemass et al, 2017) iii. Concern about ability to use telemonitoring for older patients and/or patients with less experience with technology (Barrett D, 2015;Wiegel et al, 2021) • Frustrations due to slow down of the device (Jalil et al, 2019) • Lack of internet access (Kato et al, 2015;Kruse et al, 2020;Ruberti et al, 2021) • Errors while measuring:…”
Section: Fault Tree Analysismentioning
confidence: 99%
“…• Lack of digital literacy/skills (Barrett D, 2015;Dauletbaev et al, 2021;Kruse et al, 2020;Middlemass et al, 2017;Ruberti et al, 2021;Wiegel et al, 2021). This barrier has been also mentioned as an impactful factor by Kruse et al (2020).…”
mentioning
confidence: 99%